Analisis Pengaruh Kompetensi, Independensi, Akuntabilitas, Pengalaman Dan Motivasi Auditor Terhadap Kualitas Audit (Studi Empiris Pada Kantor Inspektorat Kabupaten Grobogan) - Maulana, Kevin Iqbal; , Dr. Fatchan Achyani, SE, M.Si (2016)
The purpose of this study was to examine the influence of competence, independence, accountability, experience and motivation to audit quality Inspectorate of Regency Grobogan. The study population was Grobogan Regional Inspectorate officers who helped carry out regular checks. Data Obtained from the questionnaire which distributed to respondents. Data were analyzed using multiple linear regression analysis. The results showed that the motivational effect on audit quality. This shows that the motivation may affect both the poor quality of the audit at the offices of the inspectorate. While variable competence, independence, accountability, experience has no effect on audit quality.